Etruscan Bronze Mirror Fragments: Lasa and the Construction of Gender and Androgyny - Cottignoli, Emilia R. (Tufts Archival Research Center, 2022)
This thesis identifies an object in the Tufts Permanent Collection as an Etruscan bronze mirror from the 3rd century BCE. My work situates the fragments into the existing canon of Etruscan bronze mirrors, critically positioning it in relation to its comparanda. Through a sustained, archaeological examination of the fragments I assert that the figure is a Lasa and informs our conception of how the Etruscans conceived of identity through gender, androgyny, and funerary practice.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Dept. of the History of Art and Architecture and the Dept. of International Literary and Cultural Studies.; Advisor: Christina Maranci.